Australasian Conference on Information Systems 2018 2018
DOI: 10.5130/acis2018.cz
|View full text |Cite
|
Sign up to set email alerts
|

Factors discouraging participation of girls in ICT education

Abstract: Despite expanding ICT job opportunities, there has been a decrease in the proportion of girls entering into ICT study, and pursuing ICT careers. This paper explores factors that discourage participation of high school girls in ICT using a modified version of the conceptual framework based on the "STEMcell" model. The modified framework was used to create an online questionnaire which gathered data from girls and boys between the ages of 15 and 17 years studying at high school. Each section of the framework use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 8 publications
0
8
1
Order By: Relevance
“…The stereotypes on the content of education and the future career might be the explanation for contradictory results regarding young women's perception of career possibilities in the field. In some cases, research suggests that women high school students do not perceive the ICT field as a career prospect (Morton et al, 2018). However, the opposite was reported by Corneliussen et al (2021) who argue that female high school students in Norway see ICT field as well-paid employment opportunity and career development choice.…”
Section: Literature Overviewmentioning
confidence: 96%
See 3 more Smart Citations
“…The stereotypes on the content of education and the future career might be the explanation for contradictory results regarding young women's perception of career possibilities in the field. In some cases, research suggests that women high school students do not perceive the ICT field as a career prospect (Morton et al, 2018). However, the opposite was reported by Corneliussen et al (2021) who argue that female high school students in Norway see ICT field as well-paid employment opportunity and career development choice.…”
Section: Literature Overviewmentioning
confidence: 96%
“…Surprisingly, despite the ever-growing digital market and employment opportunities, the number of women pursuing ICT education and profession is decreasing (Morton et al, 2018). The number of women who studied and graduated on ICT was higher in the 80s, with a noted decrease later on (Beyer, 2014).…”
Section: Literature Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…These conceptions of female that the culture of using ICT in education is friendly to male more than female can describe why female have negative attitudes towards ICT. Furthermore, researchers revealed that female experienced less access to ICT-related tools than male [29]. The organization for economic cooperation and development (OECD) argued that there is a gap between younger age groups in ICT accessibility in learning and that the male and female tend to use their access differently [30].…”
Section: Introductionmentioning
confidence: 99%